Human development report 2011 : sustainability and equity: a better future for all. - United Nations Development Programme (New York : United Nations ; Basingstoke : Palgrave Macmillan, 2011)
The 2011 Human Development Report argues that the urgent global challenges of sustainability and equity must be addressed together - and identifies policies on the national and global level that could spur mutually reinforcing progress towards these interlinked goals. Bold action is needed on both fronts, the Report contends, if the recent human development progress for most of the world's poor majority is to be sustained, for the benefit of future generations as well as for those living today. Past Reports have shown that living standards in most countries have been rising - and converging - for several decades now. Yet the 2011 Report projects a disturbing reversal of those trends if environmental deterioration and social inequalities continue to intensify, with the least developed countries diverging downwards from global patterns of progress by 2050. The report shows further how the world's most disadvantaged people suffer the most from environmental degradation, including in their immediate personal environment, and disproportionately lack political power, making it all the harder for the world community to reach agreement on needed global policy changes. The Report also outlines great potential for positive synergies in the quest for greater equality and sustainability, especially at the national level. The Report further emphasizes the human right to a healthy environment, the importance of integrating social equity into environmental policies, and the critical importance of public participation and official accountability. The 2011 Report concludes with a call for bold new approaches to global development financing and environmental controls, arguing that these measures are both essential and feasible.--publisher's description (online).
Why sustainability and equity? -- Patterns and trends in human development, equity and environmental indicators -- Tracing the effects - understanding the relations -- Positive synergies - winning strategies for the environment, equity and human development -- Rising to the policy challenge -- Statistical annex.
"Published for the United Nations Development Programme (UNDP)."
Includes bibliographical references (p. 105-118, 175-176).
Also available free online.
Keywords: Sustainability -- Social aspects; Sustainability -- Environmental aspects; Sustainable development -- Social aspects; Sustainable development -- Environmental aspects; Sustainable development -- Statistics; Fairness -- Social aspects; Equality -- Social aspects; Globalization -- Social aspects; Globalization -- Environmental aspects